Studies on bioactivity of Chara braunii C. C. Gmelin (Charophyta) - Khalid, M.N.; Riaz, Z.; Shamee, l M. (Альгология, 2015)
Chara braunii a freshwater green algae belonging to the division Charophyta was collected from different freshwater habitats of Faisalabad region of Pakistan. Its antifungal activity was determined by using agar well diffusion method against ten fungal cultures. The results showed a significant response and promising antifungal activity of Ch. braunii against the tested fungal species. The present research work is highly significant in terms of understanding the response of important new natural sources of bioactive compounds for pharmaceutical industry and it is first comprehensive report from Faisalabad region. Chara braunii – пресноводный вид водорослей из отдела Charophyta, был собран в различных пресноводных местообитаниях Фейсалабадской области Пакистана. Антигрибковую активность этого вида изучали методом диффузии на агаре культур 10 штаммов грибов. Установлено влияние Ch. braunii на исследуемые культуры, свидетельствующее об ее антифунгальном характере. Результаты исследования важны для поиска новых природных источников биоактивных веществ, применяемых в фармацевтической промышленности. Это первое подобное исследование в регионе.